The nature and activity of liaison mental services in acute hospital settings: a multi-site cross sectional study - Sonia Saraiva; Elspeth Guthrie; Andrew Walker; Peter Trigwell; Robert West; Farag Shuweidi; Mike Crawford; Matt Fossey; Jenny Hewison; Carolyn Czoski Murray; Claire Hulme; Allan House (BMC, 2020)
Abstract Background To describe the clinical activity patterns and nature of interventions of hospital-based liaison psychiatry services in England. Methods Multi-site, cross-sectional survey. 18 acute hospitals across England with a liaison psychiatry service. All liaison staff members, at each hospital site, recorded data on each patient they had face to face contact with, over a 7 day period. Data included location of referral, source of referral, main clinical problem, type of liaison intervention employed, staff professional group and grade, referral onto other services, and standard assessment measures. Results A total of 1475 face to face contacts from 18 hospitals were included in the analysis, of which approximately half were follow-up reviews. There was considerable variation across sites, related to the volume of Emergency Department (ED) attendances, number of hospital admissions, and work hours of the team but not to the size of the hospital (number of beds). The most common clinical problems were co-morbid physical and psychiatric symptoms, self-harm and cognitive impairment. The main types of intervention delivered were diagnosis/formulation, risk management and advice. There were differences in the type of clinical problems seen by the services between EDs and wards, and also differences between the work conducted by doctors and nurses. Almost half of the contacts were for continuing care, rather than assessment. Eight per cent of all referrals were offered follow up with the LP team, and approximately 37% were referred to community or other services. Conclusions The activity of LP services is related to the flow of patients through an acute hospital. In addition to initial assessments, services provide a wide range of differing interventions, with nurses and doctors carrying out distinctly different roles within the team. The results show the volume and diversity of LP work. While much clinical contact is acute and confined to the inpatient episode, the LP service is not defined solely by an assessment and discharge function; cases are often complex and nearly half were referred for follow up including liaison team follow up.